2015
DOI: 10.1126/science.aac7660
|View full text |Cite
|
Sign up to set email alerts
|

Atomically thin two-dimensional organic-inorganic hybrid perovskites

Abstract: Organic-inorganic hybrid perovskites, which have proved to be promising semiconductor materials for photovoltaic applications, have been made into atomically thin two-dimensional (2D) sheets. We report the solution-phase growth of single- and few-unit-cell-thick single-crystalline 2D hybrid perovskites of (C4H9NH3)2PbBr4 with well-defined square shape and large size. In contrast to other 2D materials, the hybrid perovskite sheets exhibit an unusual structural relaxation, and this structural change leads to a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

74
1,223
5
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,216 publications
(1,329 citation statements)
references
References 31 publications
74
1,223
5
1
Order By: Relevance
“…Dou et al have developed additional type of 2D solution-processable materials as building blocks for future nanoscale electric and optoelectronic devices (Figure 7). [50] In this work, a C 4 H 9 NH 3 Br•PbBr 2 in DMF was diluted 100 times by a DMF/chlorobenzene (CB) dropped onto the Si/SiO 2 substrate and dried at 75 °C for 10 min. The use of cosolvent was vital because CB eventually minimizes the solubility of (C 4 H 9 NH 3 ) 2 PbBr 4 in DMF and promote crystallization.…”
Section: Wwwadvenergymatdementioning
confidence: 99%
See 1 more Smart Citation
“…Dou et al have developed additional type of 2D solution-processable materials as building blocks for future nanoscale electric and optoelectronic devices (Figure 7). [50] In this work, a C 4 H 9 NH 3 Br•PbBr 2 in DMF was diluted 100 times by a DMF/chlorobenzene (CB) dropped onto the Si/SiO 2 substrate and dried at 75 °C for 10 min. The use of cosolvent was vital because CB eventually minimizes the solubility of (C 4 H 9 NH 3 ) 2 PbBr 4 in DMF and promote crystallization.…”
Section: Wwwadvenergymatdementioning
confidence: 99%
“…Dou et al reported the large-scale synthesis of the monolayer (C 4 H 9 NH 3 ) 2 -PbBr 4 by a chemical method. [50] Along the same lines, several groups have prepared and characterized nanomaterials composed of various forms of perovskites. [51][52][53] Also, our group has recently successfully prepared a low-dimensional mixed 2D/3D perovskite using the protonated salt of amino valeric acid iodide (AVAI) as an organic precursor mixed with PbI 2 , in which a yellowish film was containing needle-like crystallite formed.…”
mentioning
confidence: 99%
“…Special micromorphologies such as 2D nanoplates, 1D NWs, 0D nanocrystals, nanonets, and inverse opals‐type structures have been carefully studied and showed superior optical properties and excellent electrical characteristics 52, 53, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65. These structures will be discussed in detail in the following sections.…”
Section: Factors Influencing Photodetectors Performancesmentioning
confidence: 99%
“…85 Yang and colleagues 91 have shown that atomically thin single-crystalline 2D organic-inorganic perovskites of square-shaped morphology can be directly grown on silicon substrates by drop casting a very dilute precursor solution followed by mild heating (Figures 7c-e). AFM images showed that the prepared 2D (C 4 H 9 NH 3 ) 2 PbBr 4 sheets exhibit single to few unit cell thicknesses due to the stacking of layers through van der Waals interactions between ligands (Figure 7e).…”
Section: Quantum Confinement In Perovskite Ncsmentioning
confidence: 99%